Evaluation of the Effect of Surgical Crown Lengthening on Periodontal Parameters - Farzane Vaziri; Ahmad Haerian; Mohammad Hossein Lotfi Kamran; Maryam Abrishami (Journal of Dental Materials and Techniques, 2015)
Background: Surgical crown lengthening is needed for teeth with subgingival caries, fractured teeth, insufficient crown length, and deep subgingival margin of failed restorations. Since there is no agreement on the effects of crown lengthening surgery on gingival parameters, the purpose of this study was to evaluate periodontal parameters in patients who needed crown lengthening surgery. Methods: Twenty patients who had healthy periodontium and needed surgical crown lengthening were included in this study. After professional dental cleaning, gingival parameters including gingival index (GI), probing depth (PD), bone level (BL), and transsulcular probing (TSP) were recorded in interproximal and keratinized gingiva (KG) in mid buccal portion. The patients were evaluated one and three months after the surgery. Results: After one and three months of the surgery, the amount of PD reduced from 2.32 mm to 1.25 mm and 1.17 mm, respectively (P=0.001). The mean of BL reduction was 0.88 mm after one month (P=0.001), but there was no reduction between 1 month and 3 months. Amounts of KG at baseline andone month later were 4.2 mm and 2.9 mm, respectively (P=0.001), and remained at the same level up to three months. TSP significantly reduced (from 3.67 mm at baseline to 2.62 mm after 1 month, and to 2.27 mm after 3 months) (P=0.001, P=0.005). Conclusion: The present  study suggests that in the presence of good oral hygiene, except BW (biological width), other parameters including PD, BL, KG, and TSP had significant changes after crown lengthening surgery in the period of 1 month and 3 months (P